(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The purpose of this article is to study modern medical treatment methods for glaucoma and evaluate their practical significance and effectiveness. It aims to analyze pharmacological and invasive approaches in diagnosing and treating glaucoma, as well as the role of modern medical technologies and equipment in this process.